The Holland Sisters Their influence on the success of their husbands Perkin, Kipping and Lapworth - Rochow, Eugene G.; Krahé, Eduard (Springer Berlin Heidelberg, 2001)
It is said that behind every successful man there stands a devoted and capable woman. The three famous chemists Perkin, Kipping and their collaborator Lapworth married three sisters: Mina, Lily, and Kathleen Holland. The three Holland sisters kept their husbands in close and very productive collaboration throughout their lives, thereby greatly increasing their scientific output. They functioned as a productive scientific family. However, the life and work of the men is thoroughly documented, but little is known about their wives. Professor Eugene G. Rochow, a world-renowned scientist, wrote this biographical historical novel with the help of a grandson, Dr. Brian Kipping. Professor Rochow did not intend to write a bare-bones biography. He took care to make the book factually accurate. Wherever there are no facts, he has not hesitated to flesh out the account with imagination and actual experience of others in order to make the text more readable